Sexually transmitted coinfections in patients with anogenital warts – a retrospective analysis of 196 patients. (15th April 2020) - Mueller, Simon M.; Menzi, Sheryl; Kind, André B.; Blaich, Annette; Bayer, Michael; Navarini, Alexander; Itin, Peter; Brandt, Oliver
Summary: Background and objectives: Anogenital warts (AGWs) are most commonly caused by low‐risk human papillomavirus (HPV) types, and although they are the most frequent viral sexually transmitted infections (STIs), little is known about STI coinfections in affected patients. We therefore sought to assess STI coinfection rates in patients with AGW, specify STI coinfections and calculate the number needed to screen (NNS) for each STI. Methods: A retrospective cross‐sectional study analyzing data sets from AGW patients treated in our clinic between 2008–2016. Results: 142/196 (72 %) patients had been variably screened for infections with HIV, HBV and HCV, Treponema pallidum, Neisseria gonorrhoeae, Chlamydia trachomatis, Mycoplasma genitalium and HSV. The STI coinfection rate in all tested patients was 24.6 %, yielding an NNS of 4.1 to detect any STI. Of note, the coinfection rate did not differ significantly between heterosexual men, homosexual men and women, respectively. The NNS for syphilis was 8.4, for HIV 14.0, for HCV 28.5 and for HBV 39.0. The NNS for asymptomatic patients tested for HSV, Chlamydia trachomatis and Mycoplasma genitalium were 1.4, 5.3 and 12.0, respectively. Conclusion: Due to the high prevalence of STI coinfections, AGW patients should be screened for other STIs.